Analysis of the results of the teachers version questionnaire survey on internationalization in higher education in China - Wang M. (Sormovo Readings- 2025: scientific and educational space, realities and prospects for improving the quality of education, 2025)
this article presents the results of a teachers survey of higher education in China, aimed at identifying the current state of internationalization processes in higher education; the satisfaction level of the higher education institutions international cooperation, programs and projects; possible ways of improving the processes have been identified.
Keywords: интернационализация; internationalization; higher education in China; высшее образование в Китае; опрос преподавателей; survey of teachers